(untitled) (Revista Direito em Debate, 2021)
This article aims to present reflections on the realization of the fundamental social rights that make up the minimum existential for foreigners in a situation of refuge, considering, in addition to the Brazilian legal framework, the initial position of the Supreme Federal Court (STF) in the Original Civil Action that is aimed at the entry of Venezuelans in Brazil, a process that is still ongoing. The deductive method was used, based on bibliographic and jurisprudential research. It is concluded that the fundamental social rights guaranteed to refugees in Law 9.474, on 07/22/1997, must be realized concretely, not involving the argument of reserving the possible for their non-compliance, in the environment of the Democratic State of Law.